The Impact of WhatsApp Usage on Academic Purposes among the Students of Higher Education Institutes of Sindh Province - Buriro, Mumtaz Ali; Abro, Irfan Ali; Shahzeb,; Ahmedani, Aijaz Akhtar; Rahoo, Liaquat Ali (The journal of contemporary issues in business and government, 2021)
Purpose- The aim of the study is to examine the use of WhatsApp for Academic performance and achievements among the students of higher education institutes (Private/Public) of Sindh province. This study used descriptive survey method to explore and describe the collected data. It utilized purposive sampling technique to gather data from this research’s respondents. The sample of the population for layering the usage of WhatsApp services and academic performance was of 175 students (respondents) that categorically were 94 students from Private Institutes and 81 students from Public Institutes.Thefindings of the study show that students of both types of Institutes are using WhatsApp application for many academic and social purposes. Academic’s purposeshow that students use WhatsApp for group discussion about class assignments, class work discussion, instructor announcements regarding the subject, examination preparation,and research publication groups. Students also use WhatsApp for sending and receiving notes, audio - video lectures and books in electronic format shared from instructor or library.